Religious involvement, stress and well-being among secondary school students / Hasmiza Abdul Majeed, Rohaya Sulaiman dan Nadiyah Hashim - Abdul Majeed, Hasmiza; Sulaiman, Rohaya; Hashim, Nadiyah (2013)
Living in this modernization and the effort to be abreast with globalization has brought many negative influences. These influences include the experience of negative mental health and stress which are alarming problems and affects all walks of life including teenagers. Few studies have shown that anxiety and depression, are among the most common ailments of graduate students transitioning to clinicians (Kjerulff & Wiggins,1976; Shapiro, Brown, & Biegel,2007; Turner et al., 2005). Therefore attention must be given on how these students are coping with their mental health and stress while they are still in school.